10.7k views
5 votes
2(x-3) = (x-1)+7 step by step explantion please

2 Answers

0 votes

Answer:

Explanation:

User Estatistics
by
5.0k points
3 votes

Answer:

x = 12

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Distributive Property

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Terms/Coefficients

Explanation:

Step 1: Define

Identify

2(x - 3) = (x - 1) + 7

Step 2: Solve for x

  1. Combine like terms [Addition]: 2(x - 3) = x + 6
  2. [Distributive Property] Distribute 2: 2x - 6 = x + 6
  3. [Addition Property of Equality] Add 6 on both sides: 2x = x + 12
  4. [Subtraction Property of Equality] Subtract x on both sides: x = 12
User Yao Zhao
by
5.0k points